Contrast Enhanced Ultrasound in Pediatric Patients: A Real Challenge - Schreiber-Dietrich, D. G.; Cui, X. W.; Piscaglia, F.; Gilja, O. H.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2014)
Ultrasound (US) imaging in the paediatric population has been a routine technique for decades, in part because of the advantages it offers over other imaging modalities. Off-label use (and its funding) is of the utmost importance in paediatrics because many drugs have not been evaluated in randomised trials in children. As a consequence such drugs are not specifically approved for use in children. This is also true for the contrast agents used in CEUS. The off-label use of CEUS in paediatric patients illustrates the need to deal with unresolved legal issues while at the same time balancing this with the need for high diagnostic performance in daily clinical routine. In addition to approved indications with a focus on the liver and Doppler enhancement, CEUS is safe and effective for the examination of many organs, as recently highlighted by the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB). This article provides a summary of the available literature describing the utility of CEUS in paediatric patients. Furthermore, we suggest the establishment of a registry to collect data on safety and applications of ultrasound contrast agents in children. A paediatric registry has recently been introduced by EFSUMB (www.efsumb.org).
Keywords: Leber; Charakterisierung; Microbubble; Richtlinien; Register